2005
DOI: 10.1007/s00359-005-0054-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine receptors in spider peripheral mechanosensilla

Abstract: Peripherally located parts of spider mechanosensory neurons are modulated by several neurotransmitters released from apposed efferent fibers. Activities of acetylcholine (ACh) synthesizing enzyme choline acetyltransferase (ChAT) and ACh degrading enzyme acetylcholine esterase (AChE) were previously found in some efferent fibers. ChAT activity was also present in all the mechanosensory neurons, while AChE activity was only found in some. We show that spider mechanosensory neurons and probably some efferent neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The abundances of putative ChAT and VAChT genes were relatively low in the spider CNS transcriptome and the ratio of labeled versus unlabeled neurons varied greatly throughout the CNS. Together with previous reports of cholinergic markers, such as ChAT, AChE and muscarinic ACh receptors in the spider mechanosensory and efferent neurons (Fabian and Seyfarth 1997; Fabian-Fine et al 2002; Widmer et al 2006) our findings establish the importance of cholinergic neurons for the functions of spider central and peripheral nervous systems. Furthermore, we have extended previous research on the distribution of FMRFamide related peptides in the spider nervous system (Becherer and Schmid 1999; Barth 2002) and demonstrated that they are co-localized with some anti-VAChT labeled neurons in the CNS.…”
Section: Discussionsupporting
confidence: 88%
“…The abundances of putative ChAT and VAChT genes were relatively low in the spider CNS transcriptome and the ratio of labeled versus unlabeled neurons varied greatly throughout the CNS. Together with previous reports of cholinergic markers, such as ChAT, AChE and muscarinic ACh receptors in the spider mechanosensory and efferent neurons (Fabian and Seyfarth 1997; Fabian-Fine et al 2002; Widmer et al 2006) our findings establish the importance of cholinergic neurons for the functions of spider central and peripheral nervous systems. Furthermore, we have extended previous research on the distribution of FMRFamide related peptides in the spider nervous system (Becherer and Schmid 1999; Barth 2002) and demonstrated that they are co-localized with some anti-VAChT labeled neurons in the CNS.…”
Section: Discussionsupporting
confidence: 88%
“…We will need correlative light and electron microscopic investigations to examine whether GABA-and glutamate-IR presynaptic boutons contain mixed vesicle populations and whether their axons synapse only upon the muscle fibers or also with each other. For the moment, the diversity of vesicle shapes and sizes seen in electron micrographs suggest that both vesicle types may cohabit the same terminal, possibly alongside those containing other neurotransmitters, such as octopamine, serotonin and acetylcholine (Seyfarth et al 1990;Widmer et al 2005Widmer et al , 2006.…”
Section: Discussionmentioning
confidence: 97%
“…The neurons themselves are presumably efferent, and run in parallel to the sensory neurons, forming exceedingly complex patterns of anatomical synaptic interaction (Fabian-Fine et al 1999a, b, 2002. In electrophysiological experiments, application of GABA, glutamate, octopamine and acetylcholine have all been shown to modify the sensitivities of mechanosensory neurons by acting on a variety of ionotropic and metabotropic receptors (Panek et al 2002(Panek et al , 2003Panek and Torkkeli 2005;Widmer et al 2005Widmer et al , 2006. Immunocytochemistry has revealed the expression of several different types of transmitter receptors on the sensory neurons as well as in surrounding efferent and glial cells.…”
Section: Introductionmentioning
confidence: 97%
“…In the spider, OCT increases the overall sensitivity of mechanosensory neurons by local release from efferent endings (60). This local release suggests that sensory input from specific sensilla relative to others can be emphasized depending on behavioral circumstances.…”
Section: Discussionmentioning
confidence: 99%